Investigation into laser triggering of high voltages - West, Nicholas John (My University, 2006)
In this thesis, laser-triggering of spark gaps was investigated. In other words, the purpose of the project, was to ascertain what type of laser (in terms of wavelength, energy and pulse width) is the most efficient to accomplish elec-trical breakdown across a short spark gap. The spark gap used was set up in a coaxial geometry and the gap length was able to vary from 20 mm to 2.5 mm or less. Two lasers were used: A KrF excimer (248 nm - UV) and an Nd:YAG (1064-532-355 nm). Experiments showed that a gap of 5 mm in air and a focusing lens of 100 mm, yielded the best (widest) voltage breakdown range. It was found that the key element that will ensure electrical breakdown in a spark gap, was power density (W/cm2). A power density of about 10 GW/cm2 is needed to create a spark in air. In the case of the KrF laser, the voltage range was found to be 2-13 kV (216 mJ/pulse). In the case of the YAG laser operating at 1064 nm (170 mJ/pulse), the range was 600 V-13 kV and for 532 nm (40 mJ/pulse), 3 kV-13 kV. The wavelength of the laser did effect the result. For 1064 nm, breakdown in air occured at 70 mJ, whereas at 532 nm, breakdown occured at 40 mJ. For the case where the SF6 gap was used, the range was found to be much larger than in the case of air. This can be attributed to the sensitivity of this gas to high intensity electric fields.
Master of Science in Engineering - Engineering
Keywords: voltages; triggering